Analysis of The Best Strategy for Great Education Policy Using Prescriptive Analytics (Indonesian School Experience) - Marjuni; Adly Rosyad Fudhulul Ulwani (Journal of Social Transformation and Regional Development, 2022)
This paper discusses an analytical prescriptive approach to analyzing education policy. This study uses an appropriate literature review method so that the results of the study are in the form of an overview based on a critical analysis of the subject matter of the benefits of prescriptive analytics in the field of Islamic education management. The main issues discussed in this study include a prescriptive analytics approach as an educational policy analysis approach, a prescriptive approach model in education policy analysis, and the advantages and disadvantages of a prescriptive approach in education policy analysis. This study finds that a project manager must undertake prescriptive analytics today and in the Industry 4.0 era. However, managers have a weakness in skills in this area because the future of data analysis is prescriptive, despite the impact of the obligation to change management. Research advises education managers to realize that prescriptive analytics is not always correct. Prescriptive analytics products can only be applied to one educational institution. However, the domino effect of prescriptive analytics has many benefits for educational institutions, both tangible and intangible.